2018
DOI: 10.1515/sjecr-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Type Granulosa Cell Tumor

Abstract: Granulosa cell tumor is a type of neoplasm, which represents 2-5% of all ovarian cancers. About 5% of these tumors are juvenile- type and usually occur to girls before puberty and to women younger than thirty years of age. There are signs premature puberty or premature emergence of secondary sexual characteristics with irregular vaginal bleeding that occur to these kind of patients. To the rare cases, like this, the occurrence of granulosa cell tumors can cause the appearance of hyperandrogenism with high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Ovarian cancers are the fourth most seen cancer in women after breast, lung and colorectal cancer [10]. Primary ovarian malignancies are originated in three subgroups according to cells they originate from: tumors of ovarian surface epithelium, germ cells, and sex cord cells [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ovarian cancers are the fourth most seen cancer in women after breast, lung and colorectal cancer [10]. Primary ovarian malignancies are originated in three subgroups according to cells they originate from: tumors of ovarian surface epithelium, germ cells, and sex cord cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…JGCT is generally seen in the first 30 years of life at median age of seven years [10]. The literature review revealed that more than 50% of patients are under 20 years old [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation